Mixed planting improves soil aggregate stability and aggregate-associated C-N-P accumulation in subtropical China - He, Yaqin; Zhang, Qianchun; Jiang, Chenyang; Lan, Yahui; Zhang, Han; Ye, Shaoming (Frontiers in Forests and Global Change, 2023)
Research on the variations in soil aggregate stability and ecological stoichiometry at aggregate scales by stand type is of great significance in investigating the distribution, limitation, balance, and cycling of organic carbon, nitrogen, and phosphorus (C-N-P). However, the effect of pure and mixed Chinese fir plantations on soil aggregate stability, organic carbon (OC), total nitrogen (TN), and total phosphorus (TP) stoichiometry characteristics at aggregate scales is still unclear. In this research, we explored the variations in soil aggregate mean weight diameter (MWD) and geometric mean diameter (GMD); soil OC, TN, and TP contents and stocks and the C:N:P ratios as affected by different stand types (mixed stands of Chinese fir and Mytilaria laosensis, mixed stands of Chinese fir and Michelia macclurei, and pure stand of Chinese fir); and aggregate size (<0.25, 0.25–1, 1–2, and >2 mm) at 0–20 and 20–40 cm depths in subtropical China. The soil OC and TN contents, as well as C:N:P ratios declined as aggregate size increased, whereas the C-N-P stocks showed the opposite tendencies, which were more distributed in >2 mm aggregates. Mixed stands of Chinese fir and M. laosensis with Chinese fir and M. macclurei displayed significantly higher soil aggregate stability, aggregate-associated TP content, OC and TN contents and stocks, and C:N and C:P ratios than did pure stands of Chinese fir. Soil aggregate stability was significantly positively correlated with the C-N-P contents and stocks as well as the C:N and C:P ratios, especially the C:N ratio and TN content. Overall, this work offers further information for scientific management and sustainable development of Chinese fir plantations, soil OC and nutrient cycling with ecological stoichiometry in the global terrestrial ecosystem.